FishNet: an online database of zebrafish anatomy - Robert J. Bryson‐Richardson; Silke Berger; Thomas F. Schilling; Thomas E. Hall; Nicholas J. Cole; Abigail Gibson; James Sharpe; Peter D. Currie (2007)
Over the last two decades, zebrafish have been established as a genetically versatile model system for investigating many different aspects of vertebrate developmental biology. With the credentials of zebrafish as a developmental model now well recognized, the emerging new opportunity is the wider application of zebrafish biology to aspects of human disease modelling. This rapidly increasing use of zebrafish as a model for human disease has necessarily generated interest in the anatomy of later developmental phases such as the larval, juvenile, and adult stages, during which many of the key aspects of organ morphogenesis and maturation take place. Anatomical resources and references that encompass these stages are non-existent in zebrafish and there is therefore an urgent need to understand how different organ systems and anatomical structures develop throughout the life of the fish. To overcome this deficit we have utilized the technique of optical projection tomography to produce three-dimensional (3D) models of larval fish. In order to view and display these models we have created FishNet http://www.fishnet.org.au , an interactive reference of zebrafish anatomy spanning the range of zebrafish development from 24 h until adulthood. FishNet contains more than 36 000 images of larval zebrafish, with more than 1 500 of these being annotated. The 3D models can be manipulated on screen or virtually sectioned. This resource represents the first complete embryo to adult atlas for any species in 3D.